Survival Is Worse in Patients Completing Immunotherapy Prior to SBRT/SRS Compared to Those Receiving It Concurrently or After - Woody, Susan; Hegde, Aparna; Arastu, Hyder; Peach, M. Sean; Sharma, Nitika; Walker, Paul; Ju, Andrew W. (Frontiers in Oncology, 2022)
Purpose: The abscopal effect might be potentiated when combined with immunomodulating drugs through increased antigen production. The optimal dosing and schedule of radiotherapy with immunotherapy is unknown, although it is actively investigated in laboratory/clinical settings. Clinical data in patients treated for metastatic disease with both modalities may guide future studies. Materials/methods: This is a single institution retrospective review of all patients treated with stereotactic body radiotherapy (SBRT)/stereotactic radiosurgery (SRS) and immunomodulating therapy within 6 months before or after SBRT/SRS for metastatic cancer. Clinical and tumor characteristics were recorded, as well as SBRT/SRS details, immunotherapy details, and survival. Log-rank tests on Kaplan-Meier curves for overall survival (OS) calculated from end of SBRT/SRS were used in univariate analysis, Cox proportional hazards regression for multivariate analysis. Results: 125 patients were identified who met the inclusion criteria, 70 received SBRT, 57 SRS. 83 patients were treated for non-small cell lung cancer, 7 for small cell lung cancer, and 35 patients for other cancers. 53% of patients received nivolumab, 29% pembrolizumab, 13% atezolizumab, 5% other. 20% received immunotherapy before SBRT/SRS, 39% during SBRT/SRS, 41% after. 86 patients had died by the time of analysis, The median OS for the whole cohort was 9.7 months. Patients who had completed immunotherapy prior to SBRT/SRS had worse OS than those who received immunotherapy concurrently/after SBRT/SRS, with a difference in median OS of 3.6 months versus 13.0 months (p=0.010), this was retained on multivariate analysis (p=0.011). There was no significant difference in OS between patients receiving SRS versus SBRT (p=0.20), sex (p=0.53), age >62 (p=0.76), or lung primary vs. others (p=0.73) on univariate or multivariate analysis. Conclusions: Overall survival appears to be worse in patients who complete immunotherapy prior to SBRT/SRS compared to those receiving it concurrently or after. The design of this retrospective review may be prone to lead-time bias, although the difference in median survival is longer than the 6 month window before SBRT/SRS and could only account for part of this difference. Further analysis into causes of death and toxicity and prospective studies are needed to confirm the results of this analysis.